Screening of genomic imbalances in glioblastoma multiforme using high-resolution comparative genomic hybridization - Vallová, Vladimíra; Nečesalová, Eva; Kuglík, Petr; Cejpek, Pavel; Pešáková, Martina; Budinská, Eva; Relichová, Jiřina; Veselská, Renata (Oncology reports, 2007)
Comparative genomic hybridization (CGH) is a molecular cytogenetic technique that allows the genome-wide analysis of DNA sequence copy number differences. We applied conventional CGH and the recently developed high-resolution CGH (HR-CGH) to tumour samples from 18 patients with glioblastoma multiforme (GBM) in order to compare the sensitivity of CGH and HR-CGH in the screening of chromosomal abnormalities. The abnormalities were studied in topologically different central and peripheral tumour parts. A total of 78 different changes were observed using CGH (0-16 per tumour, median 3.5) and 154 using HR-CGH (0-21 per tumour, median 6). Using HR-CGH, losses were more frequent than gains. The representation of the most prominent changes revealed by both methods was similar and was comprised of the amplification of 7q12 and 12q13-q15, the gain of 7, 3q and 19, and the loss of 10, 9p, and 13q. However, HR-CGH detected certain other abnormalities (the loss of 6, 14q, 15q and 18q, and the gain of 19), which were rarely revealed by CGH. Using HR-CGH, the numbers and types of chromosomal changes detected in the central and peripheral parts of GBM were almost the same. The loss of chromosomes 10 and 9p and the gain of chromosomes 7 and 19 were the most frequent chromosomal alterations in both tumour parts. Our results from the GBM analysis show that HR-CGH technology can reveal new, recurrent genetic alterations involving the genes known to participate in tumorigenesis and in the progression of several human malignancies, thus allowing for a more accurate genetic characterization of these tumours.
Keywords: glioblastom; Brain Neoplasms; Male; genom lidský; hybridizace in situ fluorescenční; nádory mozku; Sequence Analysis, DNA; chromozomální aberace; sekvenční analýza DNA; Nucleic Acid Hybridization; Adult; Aged; dospělí; mužské pohlaví; senioři; hybridizace nukleových kyselin; Genome, Human; Chromosome Aberrations; lidé; ženské pohlaví; Humans; Financing, Organized; In Situ Hybridization, Fluorescence; Female; cytogenetické vyšetření; financování organizované; lidé středního věku; Glioblastoma; Cytogenetic Analysis; Middle Aged